The effects of repetitive transcranial magnetic stimulation in the treatment of depression. (January 2011) - Fitzgerald, Paul B; Daskalakis, Zafiris J
Repetitive transcranial magnetic stimulation (rTMS) is currently emerging as one of the first fundamentally new treatments in psychiatric practice for a considerable number of years. Research into the use of rTMS for the treatment of patients with depression has now been conducted for over 15 years. The aim of this article was to review the development of rTMS treatment for depression and the current state of evidence supporting its use. The vast majority of the trials conducted on the technique have evaluated the efficacy of high-frequency rTMS applied to the left dorsolateral prefrontal cortex using a set of parameters very similar to those originally described in the mid-1990s. This 'standard' form of rTMS clearly appears to have antidepressant efficacy, and its effects have now been confirmed in several large-scale clinical trials and a number of meta-analyses: response is better than that of sham stimulation, although the number of responders to treatment is relatively modest. A wide range of alternative forms of rTMS have been, or are currently being, evaluated. Low-frequency stimulation applied to the right prefrontal cortex appears to have similar efficacy to standard treatment and it is possible that the bilateral approaches may prove more effective. Novel methods of stimulation, such as priming stimulation, theta-burst stimulation and deep TMS, appear to be promising although require further evaluation. Significant benefit appears likely to accumulate through the use of methods that involve a more reliable targeting of prefrontal brain regions. Research is also required to evaluate the long-term effects of rTMS treatment, its use as a maintenance therapy and to establish reliable predictors of response to treatment.